Mechanisms of facial emotion recognition in autism spectrum disorders: Insights from eye tracking and electroencephalography. (September 2017) - Black, Melissa H.; Chen, Nigel T.M.; Iyer, Kartik K.; Lipp, Ottmar V.; Bölte, Sven; Falkmer, Marita; Tan, Tele; Girdler, Sonya
Highlights: Individuals with Autism Spectrum Disorder present with atypical gaze and cortical activation to facially expressed emotions. Individuals with Autism Spectrum Disorder may use compensatory strategies during facial emotion recognition. Individuals with Autism Spectrum Disorder may employ self-regulatory strategies during facial emotion recognition. Eye tracking and electroencephalography findings may provide potential markers for diagnosis and treatment targets. Abstract: While behavioural difficulties in facial emotion recognition (FER) have been observed in individuals with Autism Spectrum Disorder (ASD), behavioural studies alone are not suited to elucidate the specific nature of FER challenges in ASD. Eye tracking (ET) and electroencephalography (EEG) provide insights in to the attentional and neurological correlates of performance, and may therefore provide insight in to the mechanisms underpinning FER in ASD. Given that these processes develop over the course of the developmental trajectory, there is a need to synthesise findings in regard to the developmental stages to determine how the maturation of these systems may impact FER in ASD. We conducted a systematic review of fifty-four studies investigating ET or EEG meeting inclusion criteria. Findings indicate divergence of visual processing pathways in individuals with ASD. Altered function of the social brain in ASD impacts the processing of facial emotion across the developmental trajectory, resulting in observable differences in ET and EEG outcomes.